TINJAUAN YURIDIS TERHADAP RESISTENSI KEPEMILIKAN TANAH DI KOTA JAYAPURA - Puspita Puspita nurfitriani; Zulfadli Zulfadli; Ade yamin (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2025)
Resistance is a form of resistance carried out by a weaker group against the ruling group. The reason the researcher conducted the research was to identify the forms of resistance, as well as the reasons for resistance to land ownership by customary rights owners and to explore more deeply the implications of the resistance. The purpose of this study is because of the resistance to migrant communities and the government by indigenous peoples, so this study will look at it through the perspective of Fiqh Siyasah. This research is included in the type of field research (Field Research), namely collecting data by utilizing the results obtained directly in the field, which is included in qualitative research. The data sources in this study come from primary data and secondary data. Based on the results of the study, the resistance that occurred in Jayapura City was carried out in four forms, namely the provision of nameplates, the installation of wooden crossbars and tree branches, the provision of banners, and road blocking. Meanwhile, the background to the resistance is the lack of knowledge about land ownership in Papua, the failure of migrant communities and the government to find the legitimate owners of customary rights, differences in interpreting land, the lack of opportunities for indigenous peoples to participate in the management of customary rights, and the loss of their livelihoods. Protection of ownership rights is in line with one of the concepts of fiqh siyasah, namely achieving justice for all people. This is related to regulations that do not favor customary rights owners as well as compensation for losses that are considered disproportionate to the value of the land being released.